ALUMNI ENGAGEMENT PROGRAM SEBAGAI UPAYA UNTUK MENINGKATKAN KUALITAS AKADEMIK PROGRAM STUDI ILMU PERPUSTAKAAN - Fadhilatul Hamdani; Nurul Hayati; Pungki Purnomo; Faiq Binar Rifqi (Program Studi Diploma Tiga Ilmu Perpustakaan Fakultas Adab dan Humaniora UIN Imam Bonjol Padang, 2023)
The purpose of this research is to examine the alumni engagement program in order to improve the academic quality of the study program. This study uses an exploratory method with a qualitative approach.. Focus Group Discussions (FGD) with alumni and interviews with the head of the Library Science Study Program, Faculty of Adab and Humanities UIN Syarif Hidayatullah Jakarta, were used to collect data. Data analysis was carried out in stages, including data reduction, presentation, and conclusion. The findings revealed that alumni of the Library Science Study Program, Faculty of Adab and Humanities UIN Syarif Hidayatullah, were involved in a variety of academic and non-academic programs, which were carried out by fellow alumni, active students, and those working with study programs. These initiatives allow alumni to stay connected to their alma mater. However, numerous programs did not run as anticipated, and other activities were unsustainable. This is because program implementation requires collaboration. As a result, the alumni involvement program in increasing the quality of the Library Science Study Program at UIN Jakarta has not been fully utilized.